Economic Transformation Toward Islamic Economics - Handi Risza; Arif Haryadi (Jurnal Ekonomi dan Perbankan Syariah, 2025)
Various scientific circles carry many socio-economic criticisms of Neoclassical economics, which reflect a failure in thinking, education, research, and policy-making that rely on Neoclassical economics. The Neoclassical economic school, which relies on economic freedom and believes too much in the superiority of market mechanisms, actually creates the danger of exploiting strong countries against weak countries, strong people against weak (marginalized) people, and aspects of morality are considered unimportant. Poverty, inequality in income distribution, environmental damage, the development of a culture of materialism and hedonism, and other social pathologies can be attributed to the peak of Neoclassical economics. Economics must be returned to its roots, namely knowledge that is based on divine values (rabbaniyah) where there is a balance between positive and normative goals to be achieved. The process of achieving human welfare still refers to the values and norms that apply in society. Thus, human welfare and happiness apply both individually and socially. The economy will return to its original function, namely providing a decent living for the community based on divine and human values within it.